Aanalisis Kinerja Keuangan Pemerintah Desa Di Kabupaten Jepara (Studi Kasus Pemerintah Desa Jambu) - Rohman, Fatchur (University of Merdeka Malang, 2020)
Financial performance, namely providing direction on financial performance, providing an assessment of performance measures to government management, providing input or evaluation of performance achievement and improving the system on government performance. The purpose of this study is to find out the financial performance of the Jambu Village Government the object under study is the Budget Realization Report data. Jambu Village Income and Expenditure Budget 2016-2018. The method used in this study is a qualitative method using primary and secondary data. The data used in this study is the Jambu Village Budget Realization Report 2016-2018 after data is processed using financial ratios in the form of Independence Ratios, Efficiency Ratios, Dependency Ratios, Activity Ratios, and Growth Ratios. Results from the 2016-2018 Jambu Village Financial Performance Analysis study showed that the Independence Ratio was very poor, the Efficiency Ratio was good or Efficient, the Dependency Ratio was very high to the Provincial or District Governments, the Activity Ratio was still unbalanced between the Ratio of Direct Shopping and Indirect Expenditure The Activity Ratio is Dominant Direct Spending, PADes rowth Ratio for 2016-2017 is very Low while 2017-2018 is very high, Growth Ratio of total PADes in 2016-2017 is very low and in 2017-2018 is relatively moderate, Direct Shopping Activity Ratio 2016 Ratio -2017 is very low, while 2017-2018 is very high while the Indirect Expenditure Activity Ratio for 2016-2017 is relatively moderate. Whereas 2017-2018 is very low.Â DOI:Â 10.26905/ap.v6i1.4103